Cross-validating the Dot Counting Test Among an Adult ADHD Clinical Sample and Analyzing the Effect of ADHD Subtype and Comorbid Psychopathology. (March 2023) - Abramson, Dayna A.; White, Daniel J.; Rhoads, Tasha; Carter, Dustin A.; Hansen, Nicholas D.; Resch, Zachary J.; Jennette, Kyle J.; Ovsiew, Gabriel P.; Soble, Jason R.
This study cross-validated the dot counting test (DCT) as a performance validity test (PVT) in an adult attention-deficit/hyperactivity disorder (ADHD) clinical population and examined the effect of ADHD subtype and psychiatric comorbidity on accuracy for detecting invalidity. DCT performance was assessed among 210 consecutive adult ADHD referrals who underwent neuropsychological evaluation and were classified into valid ( n = 175) or invalid ( n = 35) groups based on seven independent criterion PVTs. The invalid group had significantly worse DCT performance than the valid group using both the standard and unrounded scoring procedure (η p 2 = . 28 ). Classification accuracy was excellent, with 54.3% sensitivity/92% specificity at optimal cut-scores of ≥14 (rounded) and ≥13.38 (unrounded). Nonsignificant DCT performance differences emerged based on ADHD subtype or the presence/absence of comorbid psychopathology. The DCT functions well as a nonmemory-based PVT in an ethnoracially diverse ADHD population, supporting its clinical utility for detecting invalid neurocognitive performance during ADHD evaluations.